MODEL OF THE USE OF INFORMATION TECHNOLOGY IN IMPROVING THE ABILITY OF STUDENT (Experimental Study Tools Search Engine in SMA Negeri 1 Parung Bogor) - Roni Faslah (Jurnal Ilmiah Econosains, 2016)
Abstract Google is a search engine that is currently widely used in almost all Internet users when searching for information. Nearly 50% of users use the google search engine to obtain information or data. But often encountered when searching for information on google, once opened link is obtained, the information sought nothing gained even negative information such as pornography or provocation. One of the efforts undertaken so that students do not get lost in the virtual world, need to be equipped with the ability to use search engines correctly. So the information or data sought found quickly and accurately. This study aimed to analyze the differences in the ability of students before and after training in the use of tools by the search engines at SMA Negeri 1 Parung Bogor. The method used in this research is pre experimental design. The study design used is one group pretest-posttest intervention training to use search engine tools goolge. The population is all students SMA Negeri 1 Parung, Bogor Regency, amounting to 1,348. A sample of 40 respondents using purposive sampling technique. Measuring instrument used is the observation sheet. Data were analyzed by Marginal homogeneity. The results showed that the ability of the student before being given training in the use of tools google search engine with the lowest ability categories as many as 31 respondents (77.5%), while as many as nine respondents (22.5%) and high 0%. The ability of students before being given training in the use of tools google search engine with the lowest ability categories as many respondents 0 (0%), while as many as 17 respondents (42.5%) and higher by 23 respondents (57.5%). There are differences in the ability of students before and after training in the use of tools google search engine with p-value = 0.00 <Î± (0.05). Keywords: search engine, google, ability